Analisis Strategi Perusahaan dalam Pemutusan Hubungan Kerja (PHK) Terhadap Kinerja Perusahaan pada Industri Tekstil - Syifa Hoerunisa; Halimah Zahrah; Dimas Satria Iskandar; Adam Riski Mubarok (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Layoffs are often used as efficiency measures by textile companies, but their impact on company performance still needs to be studied further. This study aims to evaluate the impact of layoff strategies on operational efficiency, productivity, and sustainability of textile companies. This study aims to analyze company strategies in implementing layoffs and evaluate their impact on company performance in the textile industry sector, especially in terms of operational efficiency, work productivity, and business sustainability. This study uses a qualitative approach with the type of research article study and case study on 3 former employees of textile companies who experienced layoffs. The results of the study indicate that the layoff strategy implemented by textile companies tends to focus on short-term cost efficiency, but has an impact on decreasing employee motivation, increasing workload, and operational instability. Although financial efficiency is achieved, in the long term this strategy can reduce productivity and work loyalty, and affect the company's image. Companies are advised to design a more humanistic and communicative layoff strategy, and consider other efficiency alternatives before carrying out layoffs. A dialogue-based approach and employee retraining can help maintain the company's performance and reputation in the long term